2016
DOI: 10.1055/s-0035-1569340
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life in Patients After Treatment of Cushing’s Disease

Abstract: Former and active Cushing's disease patients suffer from a wide range of neuropsychiatric symptoms. Those symptoms might dominate the clinical picture and lead to a serious impairment in quality of life as well as extend periods of suffering and might persist even years after being found healthy. Therefore it is important to evaluate quality of life as an independent factor in every patient being affected by Cushing's disease and to include a holistic view in their therapy. Concomitant therapeutic measures sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Different studies have described higher depression and anxiety levels in comparison with literature values, healthy controls and non-functioning adenomas, measured with different questionnaires, including HADS, BDI, BDI-II and or STAI (36,37,51,75,81,82). Increased age and male gender have been related to less anxiety levels in a cohort of patients treated by transsphenoidal surgery for CD (33).…”
Section: Effects Of Remission In Quality Of Lifementioning
confidence: 92%
See 2 more Smart Citations
“…Different studies have described higher depression and anxiety levels in comparison with literature values, healthy controls and non-functioning adenomas, measured with different questionnaires, including HADS, BDI, BDI-II and or STAI (36,37,51,75,81,82). Increased age and male gender have been related to less anxiety levels in a cohort of patients treated by transsphenoidal surgery for CD (33).…”
Section: Effects Of Remission In Quality Of Lifementioning
confidence: 92%
“…Predictors for improvement in QoL after surgery were preoperative QoL impairment (meaning that patients with poorer QoL preoperatively were more likely to improve post surgery) and age (meaning that younger patients were more likely to improve post surgery) (29). Another study reported impairment in the 6 dimensions of Tuebingem 25-CD questionnaire in patients treated for CD (85% in remission after surgery) (75). In addition, women were more affected than men for the dimensions of eating behavior and cognition of the Tuebingem 25-CD questionnaire (40).…”
Section: Effects Of Remission In Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…AcroQoL Acromegaly Quality of Life Questionnaire, IQR interquartile range, SMS( +) on somatostatin analogue treatment, SMS(−) not on somatostatin analogue treatment, ↓ significantly lower compared to acromegaly patients in remission; ↑ significantly higher compared to acromegaly patients in remission, no P-value reported, = tested and no significant difference compared to patients in remission a Patients received octreotide LAR every two weeks (dose not reported) b Psychological subscales c AcroQoL scores did not differ between refractory patients and patients in remission at 24 weeks d No significant difference between all refractory patients SMS (+) or SMS (−) and patients in remission. No subgroup analysis performed for SMS(+) and SMS(−) separately e Refractory patients scored significantly lower than healthy controls f Values estimated based on figure, absolute values were not presented g Patients received weekly intramuscular injections of octreotide LAR 20 mg. At 12 weeks a dose escalation to octreotide LAR 30 mg was permitted in case GH > 2.5 ug/L and/or IGF1 above upper limit of normal for age, but this was not obligatory Chin [47] Gu [44] Guo [38] Hua [46] Psaras [49] Trepp [48] Yamamoto [45] Guo [38] SF-12 Psaras [49] Alcalar [54] Nader [50] d Psaras [49] Vega-Beyhart [52] Ye [53]…”
Section: Disease-specific Hr-qolmentioning
confidence: 99%
“…49 [42][43][44][45][46][47][48][49][50][51][52] Role physical 23 [19][20][21][22][23][24][25][26][27][28][29][30] Bodily pain 65 [60][61][62][63][64][65][66][67][68][69][70] General health 28 [22][23][24][25][26][27][28][29][30][31][32][33][34] Social functioning 53 [50][51][52][53][54]…”
Section: Physical Functioningmentioning
confidence: 99%